2021
DOI: 10.1364/ol.438954
|View full text |Cite
|
Sign up to set email alerts
|

Parametric control of a diffractive axicon beam rider

Abstract: A laser beam rider is a large-scale optical structure designed so that it is attracted toward the optical axis, while also affording forward propulsion via radiation pressure along the beam path. Such structures form the basis of laser-driven light sails. Experimental measurements are described whereby a thin diffractive axicon film is shown to exhibit a natural restoring force when its axis is displaced from the optical axis. This effect is attributed to the optical momentum change of diffracted light. Wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Srivastava and Swartzlander [20] described the optomechanics of a rigid nonspinning light sail that mitigated a catastrophic sail walk-off and tumbling using a flat axicon diffraction grating. Other recent studies by Serak et al [21], Srivastava et al [22], Chu et al [23], and Chu et al [24] confirmed the potential of this technology in the field of solar sail research.…”
Section: Introductionmentioning
confidence: 66%
“…Srivastava and Swartzlander [20] described the optomechanics of a rigid nonspinning light sail that mitigated a catastrophic sail walk-off and tumbling using a flat axicon diffraction grating. Other recent studies by Serak et al [21], Srivastava et al [22], Chu et al [23], and Chu et al [24] confirmed the potential of this technology in the field of solar sail research.…”
Section: Introductionmentioning
confidence: 66%
“…More recently, building on the above interesting results [10,12], the authors [13,14] have analyzed the performance of a Sun-facing diffractive sail in the context of minimum-time interplanetary trajectories. Many other literature works [15][16][17][18][19] demonstrate the growing interest of scientists in the diffractive sail concept. According to the recent literature [12,13], unlike reflecting solar sails, the great advantage of refractive and diffractive sails is that they can generate a large transverse component of thrust, even when facing the Sun, such as when their nominal plane is perpendicular to the Sun-spacecraft line.…”
Section: Introductionmentioning
confidence: 99%
“…Passive stabilization of lightsail dynamics via nanophotonic structures patterned onto a lightsail depicts a promising step toward attitude control. , Numerous designs for self-stabilizing flat lightsails have now been studied theoretically, including diffractive structures such as bigratings and axicons, metagratings, nonlinear photonic crystals, metasurfaces, and damped mechanical internal degrees of freedom . First experimental investigations into stable beam-riding behavior have focused on materials such as nematic liquid crystals and photopolymers on sapphire . However, for ultrathin lightsails to survive the extreme laser power densities (>1 MW/cm 2 ) for Starshot lightsail propulsion conditions, materials with ultralow absorption are required such as low-loss dielectrics and semiconductors, which can avoid substantial thermal heating, ,, in addition to thermal management strategies on enhancing the emissivity in the thermal wavelength regime. ,, …”
Section: Introductionmentioning
confidence: 99%
“…13 First experimental investigations into stable beam-riding behavior have focused on materials such as nematic liquid crystals 14 and photopolymers on sapphire. 15 However, for ultrathin lightsails to survive the extreme laser power densities (>1 MW/cm 2 ) for Starshot lightsail propulsion conditions, materials with ultralow absorption are required such as low-loss dielectrics and semiconductors, which can avoid substantial thermal heating, 1,16,17 in addition to thermal management strategies on enhancing the emissivity in the thermal wavelength regime. 16,18,19 In this paper, we design, fabricate, and characterize a dielectric optical metagrating for passive stabilization based on mirror-symmetrically arranged one-dimensional metagratings (Figure 1a).…”
Section: ■ Introductionmentioning
confidence: 99%